Ultrasound Evaluation of Quadriceps Muscle Dysfunction in Respiratory Disease. Issue 1 (January 2019) - Parry, Selina M.; Burtin, Chris; Denehy, Linda; Puthucheary, Zudin A.; Bear, Danielle
Abstract : Purpose: Peripheral muscle dysfunction can encompass reductions in muscle mass, strength, endurance, and fatigability, and is common in both critical illness and chronic respiratory diseases. There is growing interest in nonvolitional methods to quantify the severity of peripheral muscle dysfunction—in particular, the utility of ultrasonography. This review provides an up-to-date narrative synthesis of current knowledge around ultrasonography methodology and the quantitative and qualitative measures that can be obtained from ultrasound imaging. The application of ultrasonography in chronic respiratory disease and critical illness will be discussed alongside the need for standardized methodologies. Summary: Quadriceps muscle dysfunction is multifactorial with changes in muscle quantity and quality impacting on patient clinical outcomes. There is significant variability in ultrasonography image acquisition and analysis methodologies, which requires standardization. Ultrasound imaging is a promising evaluation tool that may enable identification of individuals at highest risk of muscle dysfunction and thus targeting of intervention resources. Conclusion: Ultrasonography is noninvasive and easily integrated at the bedside in clinical practice. A range of quantitative and qualitative parameters can be assessed to provide detail on severity of peripheral muscle dysfunction in respiratory disease. There is significant variability in the application of ultrasonography, in order for the field to progress standardized approach to ultrasonography needs to be developed. Abstract : Supplemental Digital Content is Available in the Text.